The Work Environment of Hospitals and the Difficulty of Dealing with Patients and Its Reflection on the Psychology of Hospital Workers - Abutaleb Abdullah Abutaleb Qaisi,; Khulud Salem M Albalawi,; Abdullah Mohammad almalki,; Sara Mahdi AlDilh,; Mona Atiyah Almehmadi,; Tasnim Ahmed Hosein,; Abdullah Ali Alshehri,; Fahad Ayed Alotaibi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Hospitals and other healthcare settings represent very intricate and complicated spaces that simultaneously serve as locations to treat sick or injured patients while also functioning as work environments for medical staff, hospital employees, and visitors among many other essential roles. The intricate combination of factors such as cleanliness, design, lighting, noise levels, temperature variations, and odors contribute significantly to the overall hospital physical environment (HPE) present in these healthcare settings. These various components can exert either positive or negative influences on psychological outcomes and the mental well-being of the individuals working within healthcare environments, with the final effects often depending on aspects like the type of hospital involved, personal characteristics and traits of the individuals, along with the specific medical specialty's particular requirements. For instance, inadequate control of noise levels and temperature settings can play a substantial role in influencing patient healing rates and overall moods. Furthermore, the physical environmental conditions can have a profound impact on healthcare providers themselves, as challenges such as persistent noise in the workplace can lead to emotional distress, complications in effectively monitoring patients, and an increase in unsafe actions, all of which can adversely affect job satisfaction among healthcare staff. This intricate interplay makes the field of HPE extraordinarily important and multifaceted, underlining its implications for enhancing staff well-being, and ultimately leading to improved workplace conditions that contribute to better patient care outcomes. Methods: Labour conditions in hospitals are well known to be one of the most stressful work environments. Nonetheless, work environment studies are still in their early stages, especially studies on the impact of the hospital work environment on workers' mental health. This study measures the relationships between the hospital work environment and workers' mental health. We focus on collective working conditions and analyze not only the objective work environment but also the subjective work environment, using workers' well-being perception and giving special attention to the organization of work. We define the hospital work environment through four concepts: work content, work context, workload, and spillover, and we consider the interrelationship between work and non-work life. We try to answer if collective working conditions are important determinants of hospital health workers' well-being, job perception, satisfaction, fatigue, and self-reported mental health. The social desirability perception of a health worker is obtained and disentangled from real collective working conditions. Conclusion: The impact of hospital work environments on healthcare workers has been explored in this study. The results obtained were the result of a combination of the social exchange and the job demand-control models. It shows that stressors and job strain are associated with psychological outcomes, such as burnout, depression, and psychological distress. When workplace support, time control, and decision control do not buffer the effect of high demand, interaction job strain occurs. The psychological impacts on healthcare workers are largely due to the work content and the work context. These findings suggest that improvements in the work content and the work context of healthcare workers, which are largely determined by the work conditions, not only can improve job satisfaction, psychological well-being, and health of healthcare workers, but also can contribute to addressing acute issues, like the shortage of healthcare workers, and chronic issues, such as healthcare quality and safety. In conclusion, health policy developers and healthcare management professionals need to pay more attention to the health and well-being of healthcare workers. They should take into consideration the needs and wishes of healthcare workers. Since improving the work environment, which is largely determined by the work conditions, is costly, it may not only be possible to reduce the costs of poor health, such as absenteeism, turnover, and presenteeism, by investing in the work content and the work context of healthcare employees, but by providing a healthy work environment, hospital performance in the broadest sense also improves.